1996
DOI: 10.1002/(sici)1096-9861(19961007)374:1<41::aid-cne3>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Excess nerve growth factor in the periphery does not obscure development of whisker-related patterns in the rodent brain

Abstract: We have addressed the issue of whether or not peripherally expressed nerve growth factor (NGF) influences the formation of whisker-specific patterns in the brain by regulating the survival of sensory neurons. Transgenic mice that overexpress an NGF cDNA in the skin were examined. In these animals, excess NGF expression is controlled by promoter and enhancer sequences of a keratin gene, thus restricting the higher levels of NGF expression to basal keratinocytes of the epidermis. Twice the number of trigeminal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Under- or over-expression of these proteins can directly affect the number of viable neurons. For example, in mice that over-express NGF, twice the normal numbers of trigeminal ganglion cells survive (Jhaveri et al, 1996). BDNF overexpression alters mouse behavior and the electrophysiological responses of cells (Croll et al, 1999; Cunha et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Under- or over-expression of these proteins can directly affect the number of viable neurons. For example, in mice that over-express NGF, twice the normal numbers of trigeminal ganglion cells survive (Jhaveri et al, 1996). BDNF overexpression alters mouse behavior and the electrophysiological responses of cells (Croll et al, 1999; Cunha et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been shown that the number of surviving primary afferent ® bers is related to the amount of target tissue available for innervation (Frank and Wester® eld, 1982). More recently it has been shown that the overexpression of NGF in the skin rescues most if not all trigeminal ganglion cells (Jhaveri et al, 1996). Thus a higher concentration of individual neurotrophins or speci® c combinations of neurotrophins in skin covering the digits could allow for a higher innervation density.…”
Section: Developmental Factors In¯uencing Innervation Densitiesmentioning
confidence: 99%
“…The purpose of this paper is to begin to provide this information. The present study was carried out in mice because transgenic mice are commonly used to reveal molecular substrates for barrel-like pattern formation and information processing (e.g., Li et al 1994;Cases et al 1996;Jhaveri et al 1996;Kutsuwada et al 1996;Abdel-Majid et al 1998;Maier et al 1999;Iwasoto et al 2000;Prakash et al 2000;Fukuchi-Shimogori and Grove 2001;Ding et al 2003).…”
Section: Introductionmentioning
confidence: 99%